152 Effects of Feeding Levels in Early Gestation on PIC Terminal Sows and Litter Performance. (12th April 2022) - Ribas, Juliana; Vier, Carine M; Siqueira, Amanda P; Brun, Nevton; Lu, Ning; Dritz, Steve; Navales, Ron; Cast, Wayne R; Orlando, Uislei A
Abstract: Our objective was to determine the effects of increasing feeding levels for terminal line sows during early gestation on sow and litter performance. A total of 615 PIC L65 (213.3 kg ± 1.51) parity 1 to 3 sows were randomly assigned at weaning to 1 of 4 treatments within parity in a randomized complete block design with body weight blocks. Treatments consisted of feeding sows with daily feed allowances to meet 85, 100, 120, or 150% of the NRC (2012) maintenance metabolizable energy (MEm) requirement calculated as MEm, kcal/d = 100×(body weight, kg) 0.75 . A common corn-soybean meal-wheat-based diet with 3, 018 kcal of ME/kg and 0.63% standardized ileal digestible lysine was used. Treatments were applied from d 5 to 30 of gestation, after which they were fed according to body condition until moved to the farrowing room. Sow was the experimental unit and data were analyzed using generalized linear mixed models with the lmer and glmer functions of R. Average caliper score at weaning was 14.4 across treatments and average feed allowances were 1.6, 1.8, 2.2, and 2.8 kg/d for the 85, 100, 120, and 150% treatments, respectively. Increasing feed allowances increased (linear, P < 0.001) weight change (-1.9, 2.3, 4.9 and 7.9 kg, respectively) and caliper score change (0.0, 0.2, 0.7, 0.7 units, respectively) from weaning to d 30 of gestation. There was no evidence for treatment effects on farrowing rate, caliper score at farrowing, total born, stillborn rate, average piglet birth weight, or piglet throughput. In summary, increasing feed allowances to meet 85 to 150% of the MEm requirements during early gestation on terminal line sows resulted in increased weight and caliper change without impact in performance. Body weight seems to be more sensitive to changes in feeding levels than caliper scores up to d 30 of gestation.